Mixing Properties of Sphingomyelin Ceramide Bilayers: A Simulation Study - Metcalf, Rainer (2012)
Ceramide is the simplest molecule in the class of glycosphingolipids composed of a sphingosine backbone and acyl moiety. It plays significant roles in cell signaling, apoptosis, binding of hormones, toxins, and viruses, and many other biologically important functions. Sphingomyelin, ceramide with a phosphotidylcholine head group, is another biologically vital lipid present in the myelin sheath of nerve cell axon. Regions with high concentrations of ceramide can be formed in biological membranes composed of sphingomyelin by enzymatic catalysis with sphingomyelinase. In order to better understand the biophysical and thermodynamic properties of these molecules and their mixtures, we have preformed NPT molecular dynamics simulations of hydrated 16:0 sphingomyelin bilayers with increasing concentrations of 16:0 ceramide at 323 K, 332 K, 340 K, and 358 K. From analyses of electron densities, hydrogen bonding, NMR order parameters, partial molecular volume, and partial molecular area, we have identified possible structural changes corresponding to liquid ordered and liquid disordered phases. These structural changes are the results of changes in intra and inter molecular hydrogen bonds between SM and Cer molecules. Our results correspond to DSC experiments for sphingomyelin bilayer concentrations up to 50% Cer. Above 50% concentration, we observe conformational changes in SM headgroup similar to that of the umbrella model for lipid cholesterol mixtures.